Government.com? Multifunctional cabinet portfolio analysis of 201 national governments. Issue 6 (7th October 2019) - Roth, Steffen; Santonen, Teemu; Heimstädt, Maximilian; Clark, Carlton; Trofimov, Nikolay; Kaivo-oja, Jari; Atanesyan, Arthur; Laki, Balazs; Sales, Augusto
Abstract : Purpose: The purpose of this paper is to examine how much value national governments worldwide place on political, economic, scientific, artistic, religious, legal, sportive, health-related, educational and mass media-related issues. This knowledge is critical as governments and policies are typically expected to be congruent with the importance these issues have for society. Design/methodology/approach: Drawing on theories of polyphonic and multifunctional organization, the authors recoded and analyzed a US Central Intelligence Agency directory to test the cabinet portfolio of a total of 201 national governments for significant biases to the above issues. Findings: The results suggest that governments worldwide massively over-allocate their attention to economic issues. Originality/value: The authors conclude that this strong pro-economic governance-bias likely translates into dysfunctional governance and development at both the national and supra-national level.